1945
DOI: 10.1021/jo01180a008
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Course and Mechanism of Grignard Reactions. Xviii. The Effect of Metallic Halides on the Reactions of Grignard Reagents With 1-Phenyl-3-Chloropropane, Cinnamyl Chloride, and Phenylethynyl Bromide

Abstract: To extend the study of free hydrocarbon radicals in solution, several organic halides (l-phenyl-3-chloropropane, cinnamyl chloride, and phenylethynyl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1955
1955
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The alkyl-alkynyl cross-coupling can also be performed according to a second pathway, which involves reacting an alkylmetal with an alkynyl halide. The first attempts were carried out by reacting iodo-or bromoalkynes with Grignard reagents in the presence of cobalt salts, [3] or organocopper derivatives. [4] However, poor to moderate yields are generally obtained.…”
Section: Gørard Cahiez* Olivier Gager and Julien Buendiamentioning
confidence: 99%
“…The alkyl-alkynyl cross-coupling can also be performed according to a second pathway, which involves reacting an alkylmetal with an alkynyl halide. The first attempts were carried out by reacting iodo-or bromoalkynes with Grignard reagents in the presence of cobalt salts, [3] or organocopper derivatives. [4] However, poor to moderate yields are generally obtained.…”
Section: Gørard Cahiez* Olivier Gager and Julien Buendiamentioning
confidence: 99%
“…However, the access to halogenoacetylenes is usually easier but the sp hybridization of the triple bond confers a low reactivity to these products. Preliminary results shown that Grignard reagents reacted with haloalkynes under cobalt catalysis in low yields as reported by Kharash 9. Later, organomagnesium‐derived arylcopper reagents have been coupled to bromoalkynes under iron catalysis 10.…”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 73%
“…This result was consistent with the observation by the Kharasch group. [11] There was no significant activity difference between THF and Et 2 O solvents, but it was a little lower in toluene. This observation could be explained in terms of the relative lower solubility of Grignard reagents in toluene.…”
Section: Resultsmentioning
confidence: 88%